Strength of the HRM system: The development of a measure - Joaquim Pinto Coelho; Rita Campos e Cunha; Jorge F.S. Gomes; Anabela Gomes Correia (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: The aim of this study is to operationalize the construct Strength of the HRM System theoretically defined by Bowen and Ostroff (2004) as a set of process metafeatures to convey signals to employees about desired and appropriate work behaviors, as well as to develop and validate a questionnaire to measure it, the HRMSQ. Design/methodology/approach: Three studies contribute to this purpose. In the first study we develop a questionnaire and test it with employees from several organizations. In the second study we applied the refined questionnaire in a sample of employees from a large company, and assessed different types of validity. The final study replicated results from the second study. Findings: Psychometric properties reveal good internal consistency reliability, item reliability and construct reliability, as well as convergent and discriminant validity. Practical implications: Results indicate that the HRMSQ can be used in the study of strategic HRM. Originality/value: The HRMSQ is a friendly instrument that can help HR practitioners to assess whether the HRM system is unambiguously perceived by employees, and identify possible problem areas in terms of the implementation process. It also contributes to research in the strategic HRM field by operationalizing a construct that is likely to improve the understanding of the link between the HRM System and organizational performance.
Keywords: 650; strength of the HRM system; questionnaire validity; questionnaire development